PROFIL KONDISI FISIK ATLET PENCAK SILAT DI PSHT RAYON KEMBANGAN KABUPATEN MAGELANG - Alif Nur Wahid; Ika Nilawati; Fredy Eko Setiawan; Nur Amin (Sports Collaboration Journal, 2024)
Pencak Silat is a product of Indonesian society and part of the people's culture. therefore the culture produced is the culture of society. Community culture is a culture of mutual cooperation, kinship, unity, unity, harmony and social tolerance. Physical condition is the most important basic requirement for optimal performance. Physical conditioning exercises are designed in stages to develop optimal physical conditioning. It is difficult to perform optimally if your physical condition is not good. The research used is quantitative descriptive research with a cross-sectional design, one of the characteristics is that there is no hypothesis and the information collected is presented. This research was conducted at the PSHT Rayon Kembangan training ground RT 03 RW 16 Sumberrejo Kembangan Magelang with a population of 15 athletes. The instrument used by researchers is the TKJI measurement for ages 16-18 years. The results of measuring the physical condition profile of pencak silat athletes at PSHT Rayon Kembangan have obtained results from arm muscle strength tests for male athletes in the good category with a percentage of 20.0% and for female athletes in the moderate category with a percentage of 33.4%. In terms of abdominal muscle strength, male athletes are in the good category with a percentage of 13.3% and female athletes are in the medium category with a percentage of 6.6%. The flexibility test for male athletes is in the medium category with a percentage of 26.6% and for female athletes in the medium category with a percentage of 20.0%. The speed test for male athletes was in the poor category with a percentage of 66.6% and in the poor category with a percentage of 33.33%. The coordination test for male athletes was in the very good category with a percentage of 46.6% and for female athletes in the very good category with a percentage of 26.6%. The power test for male athletes is in the very good category with a percentage of 66.6% and for female athletes is in the very good category with a percentage of 33.33%. The endurance test for male athletes is in the medium category with a percentage of 13.3% and for female athletes in the medium category with a percentage of 20.0%. Based on the results, it can be concluded that the pencak silat athletes at PSHT Rayon Kembangan have quite good physical condition because there are still several test and measurement components that still do not meet the TKJI standards for ages 16-18 years.   Abstrak Pencak Silat merupakan produk masyarakat Indonesia dan bagian dari budaya masyarakat. oleh karena itu budaya yang dihasilkan adalah budaya masyarakat. Budaya masyarakat adalah budaya gotong royong, kekeluargaan, persatuan, kesatuan, kerukunan, dan toleransi sosial. Kondisi fisik merupakan syarat dasar terpenting untuk performa optimal. Latihan pengkondisian fisik dirancang secara bertahap untuk mengembangkan pengondisian fisik yang optimal. Sulit untuk tampil maksimal jika kondisi fisik tidak bagus. Penelitian yang digunakan adalah penelitian deskriptif kuantitatif dengan desain crossectional, salah satu cirinya adalah tidak ada Hipotesis dan informasi yang dikumpulkan disajikan Penelitian ini di lakukan ditempat latihan PSHT Rayon Kembangan RT 03 RW 16 Sumberrejo Kembangan Magelang dengan populasi 15 atlet.  Dalam penelitian ini menggunakan instrumen dengan serangkaian tes dan kondisi pengukuran fisik dengan standar TKJI berusia 16 sampai 18 tahun. Hasil pengukuran profil kondisi fisik atlet pencak silat di PSHT Rayon Kembangan telah diperoleh hasil dari tes kekuatan otot lengan pada atlet putra dalam kategori baik dengan presentase 20,0% dan pada atlet putri dalam kategori sedang dengan presentase 33,4%. Pada kekuatan otot perut pada atlet putra dalam kategori baik dengan presentase 13,3% dan pada atlet putri dalam kategori sedang dengan presentase 6,6%. Tes fleksibilitas pada atlet putra dalam kategori sedang dengan presentase 26,6% dan pada atlet putri dalam kategori sedang dengan presentase 20,0%. Tes kecepatan pada atlet putra dalam kategori kurang dengan presentase 66,6% dan kategori kurang dengan presentase 33,33%. Tes koordinasi pada atlet putra dalam kategori baik sekali dengan presentase 46,6% dan pada atlet putri dalam kategori baik sekali dengan presentase 26,6%. Tes power pada atlet putra dalam kategori baik sekali dengan presentase 66,6% dan pada atlet putri dalam kategori baik sekali dengan presentase 33,33%. Tes daya tahan pada atlet putra dalam kategori sedang dengan presentase 13,3% dan pada atlet putri dalam kategori sedang dengan presentase 20,0%. Berdasarkan hasil dapat disimpulkan bahwa atlet pencak silat di PSHT Rayon Kembangan memiliki kondisi fisik yang cukup baik karena masih ada beberapa komponen tes dan pengukuran yang masih belum memenuhi standar TKJI usia 16-18 tahun.